Transferência da tecnologia 5G na evolução das cidades inteligentes: um estudo comparativo entre Curitiba-PR e Araguaína-TO - Leite, Júlio Aires Azevedo (2025)
Smart cities use Information and Communication Technologies (ICT) to improve the quality of life of the population, optimize urban services, and strengthen citizen engagement through digital platforms and real-time feedback systems. These practices promote more transparent and participatory governance. In this context, 5G technology stands out for enabling massive and real-time connectivity, driving advancements in sectors such as urban mobility, public safety, and environmental monitoring. This research analyzes the effectiveness of 5G in the evolution of smart cities through a comparative study between Curitiba-PR and Araguaína-TO. The strategies adopted, the challenges faced, and the impacts on technological infrastructure, innovation, digital inclusion, and civic participation were investigated. The analysis was based on a systematic literature review and gray literature. The results show that Curitiba demonstrates a more consolidated use of 5G and greater integration of smart urban solutions, while Araguaína still faces structural and political barriers. This disparity highlights the importance of technology transfer as a means to ensure that technological advances contribute to sustainable development in diverse regional contexts.